Density and Attendance Frequency of Seagrass In Coastal Waters of Porto Village, Saparua Island, Central Maluku - A. Lewerissa, Yona (Agrikan Jurnal Agribisnis Perikanan, 2023)
Seagrass acts as a food source in supporting the productivity of the living creatures that lives sorrounds, rearing areas, and sediment filtering systems. The Village of Porto is one of the coastal villages that has a fairly extensive seagrass ecosystem. Seagrass, locally known as "lalamong" is located quite far from residential areas, but information about the condition of the seagrass is still lacking. So, this study aims to inventory the species of seagrass found there, analyze the density and attendance frequency and assess environmental parameters for seagrass growth. The research was conducted from January to March 2019. Seagrass data was collected using the linear quadratic transect method at the five stations and each station consisted of three transects. The results showed that seagrass beds in the research area consists of eight species of seagrass, namely Enhalus acoroides, Thalassia hemprichi, Halophila ovalis, Cymodocea rotundata, Cymodocea serrulata, Halodule uninervis, Halodule pinifolia and Syringodium isoetifolium. C. serrulata is the species with the highest density number, but the highest attendance frequency is represented by E. acoroides. S. isoetifolium is the species with the lowest density and attendance frequency. Station three has the highest seagrass density but has a low on attendance frequency. Water quality parameters (temperature and salinity) are suitable for seagrass in the coastal waters of Porto village.